PENGEMBANGAN BAHAN AJAR BERBASIS PENDEKATAN PENDIDIKAN ANTIKORUPSI MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN LOJI CIPANAS KABUPATEN CIANJUR - Karlaely, Irma; Hasbiyallah, Hasbiyallah; Sonia, Gina Aria; Nasir, Tatang Muh; Nuroh, Laelatul (Attadib: Journal of Elementary Education, 2024)
The purpose of this research is to find out whether the development of teaching materials based on an anti-corruption education approach can be linked to the learning of Islamic Religious Education at SDN Loji Cipanas, Cianjur Regency, how to use effective methods. This research is a qualitative research. The method used in this study is the Role Playing method, discussion. This data collection technique uses observation, interviews, and document review. The results of this study indicate that Islamic Religious Education teachers and students at SDN Loji Cipanas Cianjur Regency have understood the meaning of corruption and Anti-Corruption Education. Islamic Religious Education material that can be linked to Anti-Corruption Education is understanding the meaning and meaning of Honesty. The results of this study are expected to improve anti-corruption education in everyday lifeTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//